2008
DOI: 10.1093/ndt/gfm955
|View full text |Cite
|
Sign up to set email alerts
|

Anti-glutathione S-transferase T1 antibody-mediated rejection in C4d-positive renal allograft recipients

Abstract: This is the first study reporting an association between the appearance of chronic antibody-mediated renal allograft rejection and the occurrence of de novo production of anti-GSTT1 antibodies, in the absence of anti-HLA donor-specific antibodies. This fact suggests a potential role of the GSTT1 system in anti-graft immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…5 These finding were confirmed by Alvarez-Marquez et al 10 who showed that in eight renal transplants performed in the context of a GSTT1-positive donor/GSTT1-negative recipient, which resulted in graft dysfunction and CD4 þ deposition in the kidney, 75% of the recipients developed anti-GSTT1 antibodies. In three of these, no other donorspecific HLA I/II or MHC class I chain-related gene A (MICA) antibodies were detected.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…5 These finding were confirmed by Alvarez-Marquez et al 10 who showed that in eight renal transplants performed in the context of a GSTT1-positive donor/GSTT1-negative recipient, which resulted in graft dysfunction and CD4 þ deposition in the kidney, 75% of the recipients developed anti-GSTT1 antibodies. In three of these, no other donorspecific HLA I/II or MHC class I chain-related gene A (MICA) antibodies were detected.…”
Section: Discussionmentioning
confidence: 69%
“…In liver transplantation, it may lead to de novo hepatitis, 4 whereas in kidney transplantation, chronic allograft rejection has been demonstrated. 5 In this study on the GSTT1 genotype in patients undergoing HSCT for the treatment of CH, it became apparent that the frequency of graft rejection among patients with a GSTT1-null genotype was significantly greater than in patients who were GSTT1 positive. Anti-GSTT1 antibodies were demonstrated in the sera of GSTT1-null patients who experienced graft rejection, suggesting that GSTT1 mismatch between donor and recipient may result in an Ab-mediated immune response against GSTT1 displayed on transplanted stem cells in recipients with a GSTT1-null genotype.…”
Section: Introductionmentioning
confidence: 91%
“…Several GST polymorphisms have been associated with increased risk of developing autoimmune diseases, e.g., GSTM1-null and rheumatoid arthritis [25]. Antibodies against GSTT1 have been identified in the immune response in patients with the GSTT1-null genotype [26,27]. These autoantibodies were found to be more prevalent in patients with IBD and primary sclerosing cholangitis [28].…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione S-transferase T1 (GSTT1) is a member of a family of drug metabolizing enzymes, highly expressed in liver, kidney and erythrocytes. Immune recognition of the GSTT1 alloantigen has already been described in different settings such as: (I) after liver transplant between a null recipient and a positive donor with production of donor specific antibodies, in which this particular mismatch constitutes a risk factor to develop de novo immune hepatitis [13]; (II) after kidney transplant between a null recipient and a positive donor with production of donor specific antibodies, sometimes associated with chronic antibody-mediated rejection [14]; (III) in a GSTT1-null individual after receiving blood transfusions [15]; (IV) in GSTT1-null women after pregnancy [15] and in null-GSTT1 children with congenital hemoglobinopathies after HSCT resulting in graft rejection [16]. It is worth mentioning that the null allele is present in 20% of caucasian population [17].…”
Section: Introductionmentioning
confidence: 99%